Pengaruh Omzet Penjualan, Budaya Organisasi, Dan Kedisiplinan Terhadap Kinerja Pegawai Perusahaan Daerah Air Minum (PDAM) Kota Probolinggo - Wijaya, Andi Rahmat; Haris, R Abdul; Amani, Tatik; Yoga, Yunaz Farada (Universitas Panca Marga, 2024)
This study aims to determine whether sales turnover, organizational culture, and discipline affect the performance of employees of the Regional Drinking Water Company (PDAM) of Probolinggo City. The research method used is quantitative through a causal associative approach, while the respondents in this study were employees of the Regional Drinking Water Company (PDAM) of Probolinggo City. Determination of the sample using saturated sampling technique where all employees are sampled. In proving and analyzing this, validity and reliability tests, classical assumption tests, multiple linear regression analysis tests, determination coefficient tests, multiple linear regression tests, and hypothesis testing with the t test are used. The t test results show a positive and significant effect of the sales turnover variable, organizational culture, and discipline on the performance of employees of the Probolinggo City Regional Drinking Water Company (PDAM).